2003
DOI: 10.1038/sj.onc.1207217
|View full text |Cite
|
Sign up to set email alerts
|

Mammary gland development requires syndecan-1 to create a β-catenin/TCF-responsive mammary epithelial subpopulation

Abstract: Mice with a null mutation in the cell surface heparan sulfate (HS) proteoglycan, syndecan-1 (Sdc1), develop almost normally, but resist mammary tumor development in response to Wnt-1. Here, we test the hypothesis that Sdc1 promotes Wnt-1-induced tumor development by interacting with the Wnt cell surface signaling complex. Thus, the response of Sdc1À/À mammary epithelial cells (mecs) to the intracellular, activated Wnt signal transducer, DNb-catenin, was assayed both in vitro and in vivo, to test whether b-cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 38 publications
(39 reference statements)
3
75
0
Order By: Relevance
“…As mammary ductal development is impaired in these mice (Liu et al, 2003), we considered the possibility that altered lactation could slow postnatal growth. We therefore tested embryo size in pregnant Sdc1 þ /À BALB/c females (mated to Sdc1 þ /À males).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mammary ductal development is impaired in these mice (Liu et al, 2003), we considered the possibility that altered lactation could slow postnatal growth. We therefore tested embryo size in pregnant Sdc1 þ /À BALB/c females (mated to Sdc1 þ /À males).…”
Section: Resultsmentioning
confidence: 99%
“…However, Sdc1À/À mice do not phenocopy any of the mouse models that have been engineered for loss of function of these signaling pathways. We have previously shown that heparan sulfate is conjugated to other core proteins in Sdc1À/À mice (Liu et al, 2003), suggesting that this compensatory process could be responsible for the effective rescue of HS-mediated functions. Sdc1 has been variously implicated in processes that impinge upon tumor development, and has been shown to either promote or inhibit tumor development in xenograft or culture models (Bernfield et al, 1999;Whitelock and Iozzo, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other metalloproteinases may participate in this process, MT-MMPs have been reported to cleave syndecan-1 and this shedding may affect cell motility [36]. Recent reports indicate that syndecan-1 plays an important role in mammary gland development and tumor progression via its influence on the Wnt signaling pathway [37,38]. Syndecan-1 may act as a co-receptor for important cell surface molecules or ECM components and thus play a role in regulating intracellular signaling pathways.…”
Section: Mmps Modify the Cell-ecm Interfacementioning
confidence: 99%
“…Experiments by Liu et al (26) suggest that increased DKK1 expression can reduce ␤-catenin-specific transactivation. Taken together with our results, which show that DKK1 expression lowers ␤-catenin expression, we deduce that decreased expression of DKK1 in T98G cells by tenascin-C leads to the induction of the Wnt signaling pathway.…”
Section: Growth Promoting Signaling By Tenoscin-cmentioning
confidence: 99%